2016
DOI: 10.2527/jas.2015-9617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mash feeding versus pellets on propionic/butyric acid levels and on total Escherichia coli load in the gastrointestinal tract of growing pigs1

Abstract: Feed characteristics may influence the bacterial community composition and metabolic activities in the pig gastrointestinal tract, known to be associated with positive effects on the gut. Use of mash feed is associated with reduced excretion, but little is known of its effect on the population or of the mechanism of action. Our objectives were to assess the effect of feed texture combined with feed particle size on VFA profiles and levels, total count, and the presence of genes encoding virulence factors of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The strain was passaged in a weaned pig to enhance its pathogenicity. A hemolytic, Nal r colony isolated from the feces of this pig was confirmed to be positive for O149 and the virulence genes F4, STa, STb, LT by multiplex PCR as previously described [ 27 ]. This strain, designated ECL8559A, was used in the experimental challenge in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The strain was passaged in a weaned pig to enhance its pathogenicity. A hemolytic, Nal r colony isolated from the feces of this pig was confirmed to be positive for O149 and the virulence genes F4, STa, STb, LT by multiplex PCR as previously described [ 27 ]. This strain, designated ECL8559A, was used in the experimental challenge in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Fecal presence of genes encoding ETEC virulence factors STa, STb, LT, F4 and F18 was evaluated using PCR as previously described [12]. DNA was extracted by heat lysis.…”
Section: Methodsmentioning
confidence: 99%
“…Feed particle size not only impacts gastric ecology but also other parts of the GIT particularly the large intestine. Studies have demonstrated that coarse diets were strongly associated with higher propionic and butyric acid levels in the cecum and colon contents (42, 44). It is possible that coarse feed particle size may promote an increase of bacteria populations producing SCFA and, thus, contribute to gastrointestinal health by preventing the proliferation and/or virulence of harmful bacteria such as Salmonella spp.…”
Section: Impact On Gut Microbial Activitymentioning
confidence: 99%